Avaliação de alunos com Síndrome de Down da rede municipal de ensino regular do fundamental I pelo Protocolo para Avaliação de Escolares com Deficiência Intelectual (PAEDI) - Oliveira, Mariângela Castilho Uchoa de (2019)
Down Syndrome (DS) is one of the best known causes of intellectual disability, and it is associated with a series of deficits in the development and learning process, such as reasoning, problem solving, planning, understanding of abstract thinking and with that academic learning and function adaptive behavior. There are evidences that intellectual disability is the greatest challenge of teacher in the regular classroom and there are few standardized instruments that teachers have as guideline to teach these children. Although culturally considered as a homogeneous group, there is a great variability in the functioning of these people. For that reason, bringing the International Classification of Functioning, Disability and Health (ICF) into school environment can be effective. The ICF is a reference in many countries, but not in Brazil. This classification is a biopsychosocial construct that can help the teacher evaluate the student with Down Syndrome and in order to draw an individual educational plan so that the learning of these students happens in a effective way. The aim of this research was to evaluate students with Down Syndrome from 06 to 14 years of age studying in the regular primary school system of Jundiaí and Louveira, both in São Paulo state, using Protocolo para Escolares com Deficiência Intelectual - PAEDI, an protocol for the evaluation of students with intellectual disabilities. This protocol is an instrument developed based on Activities and Participation of ICF. The main results indicate a significant variability in relation to the functioning of the children observed; each one showed to have individual ability and potential, regardless of age, school and school year. In addition, PAEDI, according to teachers, this protocol demonstrates to be an important evaluation tool for students with DS.